Cobalt and copper-based metal-organic frameworks synthesis and their supercapacitor application - Sneha Tomar; Vinod Kumar Singh (Journal of Electrochemical Science and Engineering, 2024)
In this study, two different metal-organic frameworks (MOFs) were synthesized using copper and cobalt metal ions with benzenedicarboxylic acid (bdc) as a common ligand. The prepared MOFs were characterized using X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy-energy dispersive spectroscopy. Also, the electrochemical characteristics were analyzed using cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance spectroscopy methods. Structural characterizations indicate that Co-bdc MOF is composed of three-dimensional non-uniform colloids and Cu-bdc MOF has a regular three-dimensional cuboidal structure, possessing good crystalline structure. The Cu-bdc MOF exhibited a maximum specific capacitance of 171 F/g, while Co-bdc MOF showed 368 F/g at the current density of 1 A/g. The solution resistance for the Co-bdc MOF was 0.09 Ω in comparison to 1.25 Ω for the Cu-bdc MOF. Also, the Co-bdc MOF demonstrated better cycling performance by retaining 85 % of its capacity after 2000 charge-discharge cycles. In contrast, the stability of the Cu-bdc MOF was lower, with only 78 % retention in capacity. Conclusively, the Co-bdc MOF demonstrated superior specific capacitance, lower resistance, and enhanced cyclic stability in 3 M KOH electrolyte system.